EFL Teachers' Perception on the Implementation of Collaborative Writing Hortatory Exposition Text for Eleventh Graders - Yulianingsih, Diah Rahmi (RETAIN : Journal of Research in English Language Teaching, 2022)
This study was conducted to explore the implementation, the teachers’ perceptions, and the challenges they experienced during the implementation of collaborative writing. The present study is necessary to be conducted since several problems were found in teaching writing, especially in foreign language classrooms. Thus, it is crucial to understand the implementation of collaborative writing. It is beneficial for both students and teachers to overcome the problems during the teaching-learning process. Then, the teachers’ perceptions are also important to be explored because they can reveal the teachers’ strategies to manage the classroom conditions. Also, the challenges in implementing collaborative writing need to be explored since it can enlighten the readers and help them avoid the same problems during the implementation of collaborative writing. In order to establish the purpose of the study, the researcher conducted an observation using observation field notes and a semi-structured interview with two English teachers in one of the schools in Sidoarjo. The present study used a qualitative approach to describe the research objective. Based on the result of the study, it was found that the English teachers in a particular school implemented collaborative writing successfully. Then, it was found that both teachers acknowledged that collaborative writing could benefit the writing process and the students' final works. However, teachers also faced several issues during implementing collaborative writing, for instance, the limited time for teaching, the unfair issue of students’ participation, and the assessment for each student. Therefore, they need additional time to let the students share ideas and teaching training to maximize their teaching skills using a collaborative writing strategy.